Psychometric Properties of Achievement Goal Constructs for Chinese Students - Zhao, Ningning; Zhai, Yanfang; Chen, Xiaohan; Li, Meiling; Li, Ping; Ye, Kunyu; Wen, Hongbo (Frontiers in Psychology, 2020)
In Chinese schools, classes are organized with special monitors and teachers contributing to the achievement goal structure for students. This study aimed to examine the psychometric properties of perception of teachers’ achievement goal structure constructs with 3,149 Chinese students from grades 3–8. The results showed that the internal consistencies of the whole scale and subscales were low to marginal. Eight models were examined to check the constructs of the achievement goal structure (mastery, performance, and performance avoidance). Two-factor structures proved to be the best fit. Additionally, a multilevel confirmatory factor analysis proved that the achievement goal structure existed at the same time in the class student levels. Our findings supported the hypothesis that achievement goal structures are different for students with different cultures, which implies that teaching approaches should be adapted in consideration of culturally distinct learning.